DEVELOPMENT OF CELL-BASED BIOSENSORS FOR BIOCIDE DETECTION APPLICATIONS IN WASTEWATER - Patrick Morkus (My University, 2022)
Biocides, commonly used in industrial processes, are responsible for inhibiting a biologically mediated process in municipal wastewater treatment plants (WWTPs) known as nitrification. Testing wastewaters (WW) that contain biocides prior to their treatment at municipal WWTPs is critical; inhibition of nitrification may cause ammonia levels to exceed effluent limits and lead to the discharge of biocides and other chemical compounds into receiving waterways. The specific nitrification rate (SNR) batch test/nitrification inhibition test is considered the gold-standard test for this evaluation; however, it is cumbersome and requires approximately 4 hours to conduct. The focus of this thesis aims to address the critical need for the development of a rapid nitrification inhibition test by using bacteria as cell-based biosensors (CBBs). First, non-pathogenic E. coli and an off-the-shelf nucleic acid stain were used to detect three common biocides. Expanding on this work, six additional bacterial strains (nitrifying, non-nitrifying) as CBBs were selected and the combined response – a set of fluorescence signals (“fingerprint”) – were found to successfully predict the nitrification inhibition potential of real industrial wastewater samples. Furthermore, changes in bacteria concentration and salinity content were found useful in manipulating biocide detection sensitivity. Efforts were also focused on preserving E. coli: storage temperature, salinity content, and a sugar-based polymer, pullulan, were important to maintaining a high level of survival in solution format. The benefits of sugars (pullulan and trehalose) in a dry format were also investigated: a miniature (1 L) electrospinning system was used to create thin and instantly dissolvable E. coli-embedded films to detect biocides. Finally, a new technique of aerosolizing bacteria while electrospinning sugar fibers was found to be gentler at incorporating bacteria into electrospun films when compared to electrospinning alone. Thus, this new technique could serve as a promising method of preserving the bacterial strains used as CBBs to predict nitrification inhibition potential.